Pengaruh Pendidikan Aqidah Akhlak Terhadap Perilaku Siswa Kelas IX di MTSN 11 Agam - Syarif Hidayatullah; Fenny Ayu Monia; Lisa Yunita (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In order to create an exciting learning atmosphere, it is necessary to pay attention to the arrangement and arrangement of classrooms / learning. The preparation and setting of learning space should allow children to sit in groups and make it easier for teachers to move in the power to help students learn. In settings it should be noted the following: the size and form of the class, shape and size of the student bench and table, the number of students in the classroom, the number of students in each group, the number of groups in the classroom, the composition of students in groups (such as students who are smart with students who are not smart, men and women. One of the most important factors in learning to influence education. In addition, the education system is needed with the aim of forming student characteristics, because the learning process is obtained through the environment where students are in accordance with the desired conditions. The physical environment of the class is related to the creation of a good environment by designing student seats so that the classroom atmosphere is able to encourage students to study well. A teacher should be able to create a class environment that helps develop students with accurate motivational techniques and create a healthy class climate contribution. A class environment should reflect teacher personality, attention and appreciation to students.